Development of Anion Exchange Membrane Water Electrolysis and the Associated Challenges: A Review - Hua, Daxing; Huang, Jinzhen; Fabbri, Emiliana; Rafique, Moniba; Song, Bo (ChemElectroChem, 2023)
Water electrolysis technologies for hydrogen production from renewable energy play an important role in a carbon‐free energy scenario. Anion exchange membrane water electrolysis (AEMWE) is one of the most cost‐effective and promising water electrolysis technologies due to the application of efficient, non‐noble metal electrocatalysts and the fast development of anion exchange membranes (AEMs). In this review, the most recent and significant achievements in AEMWE were summarized, including the progress in enhancing AEM conductivity and understanding their degradation mechanism, and the hot topics concerning the electrocatalyst design. The key factors that affect AEMWE performance were pointed out, further challenges and opportunities have also been discussed. The expectations for future development of AEMWE devices were also addressed. Finally, this review provided valuable guidelines for developing highly active and durable electrocatalysts and advancing the fabrication of AEMWE devices. Water electrolysis reviewed: The development and challenges in anion exchange membrane water electrolysis (AEMWE) to produce hydrogen were summarized, with the emphasis on the stability and ionic conductivity of AEM, the hot topics (water dissociation, surface reconstruction and lattice oxygen mechanism) and strategies (active‐site optimization and applying magnetic field) that concern the electrocatalyst design, as well as the performance evaluation in optimized AEMWE device.